{Binding of oxalyl derivatives of beta-D-glucopyranosylamine to muscle glycogen phosphorylase b} - Hadjiloi, T; Tiraidis, C; Chrysina, E D; Leonidas, D D; Oikonomako, N G; Tsipos, P; Gimisis, T. (Bioorg. Med. Chem., 2006)
Five oxalyl derivatives of beta-D-glucopyranosylamine were synthesized as potential inhibitors of glycogen phosphorylase (GP). The compounds 1-4 were competitive inhibitors of rabbit muscle GPb (with respect to alpha-D-glucose-l-phosphate) with K-i values of 0.2-1.4 mM, while compound 5 was not effective up to a concentration of 10 mM. In order to elucidate the structural basis of their inhibition, we analysed the structures of compounds 1-4 in complex with GPb at 1.93-1.96 angstrom resolution. The complex structures reveal that the inhibitors can be accommodated at the catalytic site at approximately the same position as alpha-D-glucose and stabilize the T-state conformation of the 280s loop by making several favourable contacts to Asp283 and Asn284 of this loop. Comparison with the lead compound N-acetyl-beta-D-glucopyranosylamine (6) shows that the hydrogen bonding interaction of the amide nitrogen with the main-chain carbonyl oxygen of His377 is not present in these complexes. The differences observed in the Ki values of the four analogues can be interpreted in terms of subtle conformational changes of protein residues and shifts of water molecules in the vicinity of the catalytic site, variations in van der Waals interactions, conformational entropy and desolvation effects. (c) 2006 Elsevier Ltd. All rights reserved.